P.I. Novgorodtsev about the social ideal of K. Marx - Гараева , Галина; Корнев, Виктор (Hybris, 2018)
The article deals with a critical analysis of the social ideal of Marx in the work of the famous Russian theorist and philosopher of law living at the turn of the 19th and 20th centuries, P. I. Novgorodtsev. The social ideal of Karl Marx is discussed as the idea of «The Paradise on the Earth», the implementation of which will lead to the completion of the social progress, which is contrary to the dialectical view of historical process. Criticizing the «ideal of ultimate perfection» of Marx, Novgorodtsev proposes his «ideal of infinite perfection», based on the continuous moral work of the individual, which determines the direction of the social progress at all stages of history. The article also presents the reaction of Novgorodtsev’s contemporaries to his criticism of the social ideal proposed by Karl Marx.